Orofacial neuropathic pain induced by oxaliplatin: Downregulation of KCNQ2 channels in V2 trigeminal ganglion neurons and treatment by the KCNQ2 channel potentiator retigabine. Issue 1 (August 2017) - Ling, Jennifer; Erol, Ferhat; Viatchenko-Karpinski, Viacheslav; Kanda, Hirosato; Gu, Jianguo G
Neuropathic pain induced by chemotherapy drugs such as oxaliplatin is a dose-limiting side effect in cancer treatment. The mechanisms underlying chemotherapy-induced neuropathic pain are not fully understood. KCNQ2 channels are low-threshold voltage-gated K + channels that play a role in controlling neuronal excitability. Downregulation of KCNQ2 channels has been proposed to be an underlying mechanism of sensory hypersensitivity that leads to neuropathic pain. However, it is currently unknown whether KCNQ channels may be downregulated by chemotherapy drugs in trigeminal ganglion neurons to contribute to the pathogenesis of chemotherapy-induced orofacial neuropathic pain. In the present study, mechanical sensitivity in orofacial regions is measured using the operant behavioral test in rats treated with oxaliplatin. Operant behaviors in these animals show the gradual development of orofacial neuropathic pain that manifests with orofacial mechanical allodynia. Immunostaining shows strong KCNQ2 immunoreactivity in small-sized V2 trigeminal ganglion neurons in controls, and the numbers of KCNQ2 immunoreactivity positive V2 trigeminal ganglion neurons are significantly reduced in oxaliplatin-treated animals. Immunostaining is also performed in brainstem and shows strong KCNQ2 immunoreactivity at the trigeminal afferent central terminals innervating the caudal spinal trigeminal nucleus (Vc) in controls, but the KCNQ2 immunoreactivity intensity is significantly reduced in oxaliplatin-treated animals. We further show with the operant behavioral test that oxaliplatin-induced orofacial mechanical allodynia can be alleviated by the KCNQ2 potentiator retigabine. Taken together, these findings suggest that KCNQ2 downregulation may be a cause of oxaliplatin-induced orofacial neuropathic pain and KCNQ2 potentiators may be useful for alleviating the neuropathic pain.